JELAPEC (JELAJAH LINTASAN PECAHAN) TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATERI PECAHAN - Dwi Urinti Rondika; Novi Susanti; Helni Indrayati (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aimed to determine the effect of use of JELAPEC (Fraction track eksploration) teaching aids on students’ critical thinking skills in fraction material for grade VII. The sample of this study was grade students as the experimental class and grade students as the control class. This study used an experimental method with a pretest-posttest control group design. data collection techniques were carried out through documentation and critical thinking ability tests in the from of pretest and posttest. Data analysis used normality tests, homogeneity tests, and hypothesis tests with t tests. The results showed that students’ critical thinking skills in the experimental class were while in the control class were The results of the hypothesis test show that the use of the JELAPEC (Fraction Path Exploration) teaching aids has a significant effect on students’ critical thinking skills on fraction material. Thus, was rejected and was accepted. This shows that use of JELAPEC (Fraction Path Exploration) teaching aids is effective in improving students’ critical thinking skills for grade VII MTs Negeri 1 Pagar Alam. Keywords: JELAPEC, Critical Thinking Skills, Fraction